품종별 귀리 메탄올 추출물의 항산화 성분 및 항산화 활성 - 함현미(Hyeonmi Ham); 우관식(Koan Sik Woo); 이병원(Byongwon Lee); 박지영(Ji-Young Park); 심은영(Eun-Yeong Sim); 김병주(Byung Joo Kim); 이춘우(Choonwoo Lee); 김시주(Si-Ju Kim); 김욱한(Wook Han Kim); 이준수(Junsoo Lee); 이유영(Yu-Young Lee) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2015)
Oats (Avena sativa L.) were evaluated in recent years as a promising crop for increasing the nutritional quality of foods, due to their abundance in many bioactive compounds. The objectives of this study were to determine antioxidant compounds and antioxidant activities of nine oat cultivars and investigate the relationships between antioxidant compounds and antioxidant activities in oat cultivars. The contents of total polyphenolics and vitamin E in oat cultivars were analyzed by spectrophotometric methods and normal phase HPLC, respectively. 2,2'-Azino-bis-(3-ethylbenzothiazoline- 6-sulphonic acid) (ABTS) radical and 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging activities, reducing power, and chelating effects were used to compare the relative antioxidant activities of oat cultivars. In this study, total polyphenolic and vitamin E contents of oat cultivars ranged from 83.41 to 130.59 mg gallic acid equivalents/100 g and 0.54 to 1.90 mg/100 g, respectively. High levels of ABTS radical (116.14 mg Trolox equivalent antioxidant capacity (TEAC)/100 g) and DPPH radical (38.58 mg TEAC/100 g) scavenging activities and reducing power ($A_{700}=0.922$) were found in Daeyang. Significant correlation was evaluated between total polyphenolic contents and their antioxidant activities, namely ABTS and DPPH radical scavenging activities and reducing power. A low correlation was observed between vitamin E contents and their antioxidant activities. The results of this study could have an impact on oat consumption by enhancing consumer awareness of the health benefits of oats. 본 연구에서는 국내에서 개발된 귀리 품종의 항산화 성분 및 항산화 활성을 측정하고 항산화 성분과 활성 간의 상관관계를 분석하고자 하였다. 항산화 성분으로는 총 폴리페놀과 vitamin E 함량을 측정하였으며 항산화 활성은 2,2'-azinobis-(3-ethylbenzothiazoline-6-sulphonic acid)(ABTS) 및 1,1-diphenyl-2-picrylhydrazyl(DPPH) 라디칼 제거능, 환원력, 금속이온 제거능을 측정하였다. 총 폴리페놀 함량은 83.41~130.59 mg/100 g으로 나타났으며 쌀귀리 품종의 총 폴리페놀 함량이 겉귀리보다 높은 것으로 나타났다. 또한 vitamin E 함량은 0.54~1.90 mg/100 g으로 나타났으며 중모 2005 품종을 제외한 모든 품종의 귀리에서 ${α}$-tocotrienol의 비중이 가장 높은 것으로 나타났다. ABTS 라디칼 제거능, DPPH 라디칼 제거능 및 환원력은 대양 품종이 각각 116.14 mg TEAC/100 g, 38.58 mg TEAC/100 g 및 $A_{700}=0.922$로 가장 높은 활성을 보였다. 항산화 성분과 활성 사이의 상관분석 결과 총 폴리페놀 함량과 ABTS 라디칼 제거능(0.847, P<0.01), DPPH 라디칼 제거능(0.887, P<0.01) 및 환원력(0.653, P<0.01) 사이에 높은 상관성을 나타내어 귀리 메탄올 추출물의 항산화 활성에 기여하는 성분은 폴리페놀성 화합물인 것으로 사료된다. 본 연구 결과는 귀리의 항산화 성분과 항산화 활성 연구에 있어 기초자료로서 활용될 수 있을 것으로 생각하며, 국내 개발 귀리 품종의 이용 증진에 영향을 끼칠 것으로 기대한다.